The Impact of Aviobridge Facility on Flight Security, Safety, and Comfort - Abdillah Yoga Trenggono, Kimas; Musadek, Ahmad; Maharani Sukma, Meita (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Aviobridge is a facility used for passengers as a liaison between the departure/arrival terminal building for passengers and airplanes. Therefore, the Apron Movement Control (AMC) that provides aerobridges can facilitate the process of getting on and off passengers from airplanes while still paying attention to the security and safety of flight operations, so that using aviobridge is effective and makes passengers comfortable with the available aviobridge facilities. Broadly speaking, the purpose of this research is to look deeper into aerobridged facilities in providing security, safety, and flight comfort at Lampung Radin Inten II International Airport. This research uses quantitative methods with a description of the situation that occurs directly in the object of research. Data was obtained from direct observation, literature review, and distributing questionnaires to passengers totaling 50 respondents. The results of the calculations that have been done by the author use the Likert scale and are tested with validity tests, reliability tests, and correlation tests. The results obtained from this study that according to data that have been processed show that this aerobridged facility can provide security, safety, and comfort on flights at Lampung Radin Inten II International Airport. This is evidenced by validity tests, reliability tests, and correlation tests that have positive results that indicate that aerobridged facilities and flight security, safety, and comfort have a relationship.